Efficacy of Pulsed Radiofrequency to Cervical Nerve Root for Postherpetic Neuralgia in Upper Extremity - Ding, Yuanyuan; Li, Hongxi; Hong, Tao; Yao, Peng (Frontiers in Neuroscience, 2020)
Background: Postherpetic neuralgia (PHN) seriously affects a patient’s quality of life, and it is urgent to find a method that can effectively alleviate the PHN of the upper extremity. Objective: To observe the Efficacy of pulsed radiofrequency (PRF) to cervical nerve root for PHN in upper extremity under CT guidance. Study Design: Retrospective comparative study. Setting: Shengjing Hospital of China Medical University. Methods: Fifty patients with PHN in upper extremity were enrolled in Pain Management. Patients were randomized into 2 groups: cervical nerve root block (A group, n=25) and cervical nerve root PRF (B group, n=25). At each observation time, the general characteristics, visual analogue scale (VAS), quality of life scores assessment (SF-36), the total efficacy rate, dosage of antiepileptic and narcotic analgesics, and the incidence of complications were followed up. Results: Compared with the preoperative, the postoperative VAS decreased, the physical component summary (PCS) and the mental component summary (MCS) increased in both groups (P<0.05). The differences between group B and group A were statistically significant after 1 month, which could be maintained for 1 year (P < 0.05). The total efficacy rate of group A and group B was 52.0% and 80.0% at 1Y, respectively. The total efficacy rate of group B was higher than that of group A (P<0.05). The dosage of antiepileptic and narcotic analgesics in group B decreased significantly, and the decline was significant compared with group A (P<0.05). The incidence of complications between the two groups were similar (P>0.05). Conclusions: CT-guided PRF to cervical nerve root for the treatment of PHN in the upper extremity is safe and effective. PRF can replicate the location of pain, precise positioning, reduce trauma and increased pain relief rate.